Spontaneous Epidural Hematoma of the Cervical Spine Mimicking a Cerebrovascular Accident: A Case Report - Jamali, Mohammad; Entezam, Sepehr; Ghahramani, Sulmaz (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Objective The present study is a case report of a 57-year-old female with controlled hypertension who presented with spontaneous spinal epidural hematoma (SSEH) mimicking a cerebrovascular accident (CVA) and was successfully treated by surgical decompression.Methods A 57-year-old woman with a medical history of hypertension presented with a sudden onset of weakness in the right upper and lower extremities. Weakness of grade 3/5 was noted in her right upper and lower extremities, but there was no motor weakness of the right facial muscles. A magnetic resonance imaging (MRI) exam of the cervical spine revealed an epidural hematoma extending from level C5 to level C7, causing spinal cord compression.Results During surgery, a cervical spinal epidural hematoma (SEH) was evacuated. Postoperatively, the power in both limbs improved to grade 5/5 just after surgery.Conclusions A high degree of suspicion, meticulous history taking, and physical examination have a great importance in these rare conditions because anticoagulant therapy as a routine treatment for ischemic CVA could be life-threatening.
Keywords: spontaneous spinal epidural hematoma; cervical spine